Parte-Iščica, archaeological and dendrochronological investigations - Velušček, Anton; Čufar, Katarina; Levanič, Tom (Arheološki vestnik, 2000)
Archaeological and dendrochronological investigations were carried out at part of the late Eneolithic settlement of Parte-Iščica in the Ljubljana Moor. It is located along the Iščica Stream. The pottery finds correspond in terms of characteristics to those from the site of Parte. From a total of 1237 piles belonging to 12 species of trees, we succeeded in acquiring relative dates for 285 specimens, and composed two ash and one beech chronologies, 136, 113 and 105 years long, respectively. With the help of the relative dendrochronological dates and the horizontal stratigraphy, we reconstructed the plans of nine dwellings buildings from various periods. The first radiocarbon dates for a further ash chronology confirm that the pile-dwelling settlement remains are dated to the first half of the 3rd millennium BC.